RANCANG BANGUN RANGKA MESIN PENGERING GABAH PADI (BED DRYER) KAPASITAS 3 KG - Syafwan, Elvathna; Ramdani, Rizki; Saleh, Agus; Jumaati, Muhammad Quraish (Jurnal TEDC, 2023)
In the process of harvesting rice, farmers take rice grains or grain to dry. For small-scale farmers, grain drying is done manually with the help of solar heat. It is not effective because it depends on weather conditions. Rice grain drying machines on the market are generally for large capacities. This machine is not suitable for small scale farmers. Based on this background, a rice grain drying machine was designed for small production scale farmers. The limitations of this study only discuss the construction of the engine frame. The stages of the research carried out are; determine the initial specifications of the rice grain drying machine, make a design and test the design of the machine frame using Autodesk Inventor Professional 2017, manufacture the frame of the rice grain drying machine.